Penerapan Algoritma Apriori terhadap Penjualan Obat pada Apotek Cahaya Paris Berbasis Web - Rahmanda, Habib; Ok Muhammad Ihsan (Universitas Methodist Indonesia, 2025)
Cahaya Paris Pharmacy sells both prescription and non-prescription drugs. A common problem at Cahaya Paris Pharmacy is the mismatch between stock and demand, causing some drugs to rarely leave shelves until their expiration date. The drug sales data management system is not yet computerized, resulting in inefficient sales reports and errors. The pharmacy has not yet implemented the Apriori Algorithm method to analyze patterns in existing transaction data. To address these issues, Cahaya Paris Pharmacy requires a web-based system that implements the Apriori Algorithm method. The resulting drug sales system is capable of analyzing drug sales patterns using the web-based Apriori Algorithm method. The resulting sales patterns aim to recommend drugs to customers, provide discount strategies, and develop the pharmacy's ability to manage transaction data using the Apriori Algorithm method for easier and more accurate calculations.